Estudos dos impactos ambientais negativos gerados no ciclo de operações do armazenamento de grãos - Dantas, Jéssica Sousa (Universidade Federal Rural do Semi-Árido, 2017)
Known worldwide for its grain production, in addition to its agricultural frontiers, Brazil must expand its grain storage units, allowing a greater commercialization power of agricultural products. This work has as main objective to list the negative environmental impacts generated in the operations cycle of storage units of grain and to suggest mitigating measures for each impact found. Through a bibliographical review each step was analyzed and studied, generating individual flow charts where their main negative impacts are found. In the literature, there is a lack of information on the impacts generated in the cycle of grain storage operations. The present paper lists the main negative environmental impacts through individual flow charts for each step, and suggests mitigating measures that are economically feasible.
Monografia
Keywords: Unidade armazenadora; Armazenamento; Impactos ambientais; Medidas mitigadoras; Storage unit; Storage; Environmental impacts; Mitigating measures; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA